The Understanding of Lecturers of Indonesian Christian University of Maluku on Google Scholar and Science and Technology Index (SINTA) - Godprit H. Touwely; Laisila, Maya; Amelia Tahitu; Anamofa, Jusuf N.; Purimahua, Sarlota Y.; Nanuru, Ricardo F. (International Journal of Psychosocial Rehabilitation, 2020)
The development of higher education in Indonesia since the change of the Ministry of Education and Culture (Kemendikbud) to the Ministry of Research, Technology and Higher Education (Kemenristekdikti) seems very fast. One item that is seen developing, for example in the field of publication, that moves quickly against neighboring countries in the ASEAN sphere. This development must of course be supported by all parties under the umbrella of this ministry, including the Indonesian Christian University of Maluku (UKIM). The problem in this research is why after two years and four months of launch (since 30 January 2017), there are still lecturers at UKIM (as of May 2019, 62 lecturers recorded in forlap) who do not have a SINTA account? The purpose of this study was to find the root of the problem related to not having SINTA account by 62 lecturers at the Indonesian Christian University of Maluku. This type of research was qualitative one that raised ideographically the phenomena about 62 lecturers from Indonesian Christian University of Maluku (UKIM) haven’t been registered yet on SINTA Ristekdikti portal. Based on the research conducted until December 2019, there was an addition of 12 lecturers registered in SINTA so the informants, who were before 62 people in number, became 54 people (4 of whom have just registered in PD Dikti UKIM). Out of 54 informants, only 31 whose data have been collected successfully due to a variety of reasons. This research results showed that lecturers who do not have SINTA account departed from these two major reasons, which were email account having ukim.ac.id domain and Google Scholar. This research then had novelty value from which it was found that not all lecturers had the ability to manage various career needs, especially the one connected to information technology system, so they need to be guided by competent people or institutions at UKIM Ambon.